Read and Understand: How a Simple Strategy Transforms Pupils’ Reading Skills - Cabiera, Ma. Arabella Avril I.; Aurellano, Jesus O.; Bacnat, Hashlyn Joy T.; Cacuyong, Florence D.; Palaspas, Christine Mae D.; Fernando, Madeline (CV. Doki Course and Training, 2025)
This research examined the effectiveness of the READ (Read, Examine, Analyze, and Deliver) strategy in enhancing reading comprehension among Grade IV pupils. A total of 45 participants were purposively selected from Caraitan Integrated School, Nagrebcan Elementary School, Mariano Marcos Memorial Elementary School, and Garnaden Elementary School in Ilocos Norte, Philippines, based on their low pre-assessment scores. The primary objectives were to assess pupils’ reading comprehension levels through a pretest and to explore their learning experiences and improvements after the strategy’s implementation. A mixed-methods research design was employed. Quantitative data were collected from pretest and posttest results and analyzed using descriptive statistics. Qualitative data, obtained from interviews and pupils’ journals, were analyzed thematically. The findings indicated a marked improvement in reading comprehension of English stories following the application of the READ strategy. The posttest mean score (13.64) substantially exceeded the pretest mean score (5.80), resulting in a significant mean difference of 7.84. Thematic analysis revealed key insights into pupils’ learning experiences, highlighting increased engagement, improved comprehension skills, and greater reading confidence. Pupils reported that the strategy’s structured, step-by-step process facilitated deeper understanding of texts and fostered active participation in reading activities. In conclusion, the READ strategy proved to be a highly effective pedagogical approach for improving reading comprehension among elementary pupils, particularly those with initially low proficiency levels. The integration of quantitative gains and qualitative feedback underscores its potential applicability in broader educational contexts to promote literacy development in primary education.